Infection of the Upper Respiratory Tract with Seasonal Influenza A(H3N2) Virus Induces Protective Immunity in Ferrets against Infection with A(H1N1)pdm09 Virus after Intranasal, but Not Intratracheal, Inoculation - Bodewes, Rogier (American Society for Microbiology, 2013)
The clinical symptoms caused by infection with influenza A virus vary widely and depend on the strain causing the infection, the dose and route of inoculation, and the presence of preexisting immunity. In most cases, seasonal influenza A viruses cause relatively mild upper respiratory tract disease, while sometimes patients develop an acute severe pneumonia. Heterosubtypic immunity induced by previous infections with influenza A viruses may dampen the development of clinical symptoms caused by infection with influenza A viruses of another subtype, as is the case during influenza pandemics. Here we show that ferrets acquire protective immunity after infection of the upper respiratory tract with a seasonal influenza A(H3N2) virus against subsequent infection with influenza A(H1N1)pdm09 virus inoculated by the intranasal route. However, protective heterosubtypic immunity was afforded locally, since the prior infection with the A(H3N2) virus did not provide protection against the development of pneumonia induced after intratracheal inoculation with the A(H1N1)pdm09 virus. Interestingly, some of these animals developed more severe disease than that observed in naïve control animals. These findings are of interest in light of the development of so-called universal influenza vaccines that aim at the induction of cross-reactive T cell responses.